Smallwood Interview 04B - Memorial University of Newfoundland. Educational Television Centre
Robert Pitt continues his interview with Joseph (Joey) Smallwood. In this segment Smallwood talks about living in New York and London and his exposure, mainly through public lectures, to a great variety of different philosophies, ideas and theologies. He attended meetings of the "Spiritualists" with Lady Helena Squires in London and then later in Toronto. Smallwood discusses his thoughts on different religions generally and how religion affected politics in Newfoundland. Also, speaks of Norman Squires, son of Sir Richard Squires.